Probiotics in Integrative Medicine: Bridging the Gap Between Traditional and Modern Approaches - Balamurugan, Bhavani Sowndharya; Chinnakannu Marimuthu, Mathan Muthu; Anbalagan, Saravanan; Agaram Sundaram, Vickram; Chopra, Shivani (Scripta Medica, 2025)
As a transformational gateway between traditional and modern approaches within the field of integrative medicine, this review article investigates the incorporation of probiotics into healthcare procedures. The research traces the historical origins of probiotics in fermented foods and traditional medicines and explains how they evolved to be used in modern applications, demonstrating the dynamic continuity of knowledge. Mechanistic insights provide the scientific basis for the incorporation of probiotics into holistic healthcare methods by highlighting their considerable impacts on immunomodulation, metabolism and gut flora. The potential to combine traditional healing methods with evidence-based medicine is demonstrated via case studies and collaborative models including both contemporary practitioners and traditional healers. Probiotics' effectiveness in integrative healthcare is critically assessed in this paper, which highlights the benefits of both traditional and modern viewpoints. It emphasises the value of patient education and cultural awareness while addressing possibilities, problems and regulatory issues. Presented work supports continued investigation into the connections between probiotics, conventional medicine and traditional practices in order to further the development of patient-centred and culturally sensitive integrative healthcare approaches.
Keywords: Probiotics; Gastrointestinal microbiome; Integrative medicine; Healthcare; Fermented foods